This one seems pretty straightforward. We're given that[(x - 5)(x + 2)]/[(x + 5)(x - 2)] = 1Multiply the equation by the denominator, and we get(x - 5)(x + 2) = (x + 5)(x - 2)Use FOIL to multiply each side out, and we see thatx^2 - 3x - 10 = x^2 + 3x - 10Subtract (x^2) and add 10 to both sides, and we're left with-3x = 3xfor which only one solution is possible:x = 0Since x = 0, Quantity A is 5Quantity B is 4...so the answer is (A).

Post a Comment

## 1 comment:

This one seems pretty straightforward. We're given that

[(x - 5)(x + 2)]/[(x + 5)(x - 2)] = 1

Multiply the equation by the denominator, and we get

(x - 5)(x + 2) = (x + 5)(x - 2)

Use FOIL to multiply each side out, and we see that

x^2 - 3x - 10 = x^2 + 3x - 10

Subtract (x^2) and add 10 to both sides, and we're left with

-3x = 3x

for which only one solution is possible:

x = 0

Since x = 0,

Quantity A is 5

Quantity B is 4

...so the answer is (A).

Post a Comment